(3GdQNGeGJ GdCabjIs - (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s
(3ChdgG (B:s
(3GdQNGeI Ydi SWM eYdhe GdhVY Ph TNU bGFe s
(3BNQgG (B:s
(3dcf ZQVfG ai gPG Gdbhd PcQ GdLed hGdCUhd GdJi jYJeO YdjgG ai Yed GdQNGeGJ JSJhai Njg LejY GdeYGfi hGdCZQGV hGdCYeGd GdJi JbJVjgG gPg GdUfGYI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(1 / 3934) s
Keywords: (3Gdadcs